Estimationof the production of capim dourado(Syngonanthus nitens) to subsidizeits socioeconomically sustainable extractivism in the Jalapão State Park, TO - Santana, Helena Maria de Paula; Sano, Edson Eyji; Oliveira Júnior, Manuel Pereira de; Lacerda, Marilusa Pinto Coelho (Sociedade & Natureza, 2018)
The exploration of capim douradocorresponds to one of the most important economical activities in the Jalapão region, Tocantins State. This study aimed to estimate the production of capim douradoin the Campos Limpos Úmidosassociated to Veredas in the Jalapão State Park. The productivity was estimated from 20 sites over the Campo Limpo Úmidoin the years of 2011 and 2012. Along the transects perpendicular to the streams located in areas dominated by Campos Limpos Úmidos, we sampled stems of capim douradowithin a set of sampling areas of 0.5 m x 0.5 m. The stems were oven-dried and weighed to calculate the dry biomass (productivity). The production was estimated multiplying the area occupied by Campos Limpos Úmidosby the average productivity of stems. We also interviewed 70 affiliates of local associations of handicrafts and extractors registered in the Jalapão region. Theproduction, estimated in 125,696 kg, can be considered high if we compare tothe average amount of capim douradoexplored by local associations registered in the environmental agency of Tocantins State, which is approximately 20,250 kg ano-1. This is about 16% of the amount produced in the Park. Considering that the exploration is increasing in the region, a more tight control of such exploration inside the Park is recommended.